2020
DOI: 10.1039/c9ra08268a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based artificial SEI layers for aqueous lithium-ion battery anodes

Abstract: Artificial SEI layers passing lithium ions but blocking water molecules for long-lasting aqueous lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The best battery performance achieved with m-TiO 2 electrodes was comparable to the battery performance obtained with the carbon-coated TiO 2 electrodes made of glucose (Figure S12) 22 but using 11% less carbon in the composite. One of the most obvious characteristics of this microbe-derived carbon layer is a high concentration of nitrogen, corresponding to a peak at 398.58 eV from XPS N 1s spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The best battery performance achieved with m-TiO 2 electrodes was comparable to the battery performance obtained with the carbon-coated TiO 2 electrodes made of glucose (Figure S12) 22 but using 11% less carbon in the composite. One of the most obvious characteristics of this microbe-derived carbon layer is a high concentration of nitrogen, corresponding to a peak at 398.58 eV from XPS N 1s spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
“…Furthermore, it has been reported that the SEI layers on TiO 2 particles in WIS-based LIBs were made of disconnected arrays of inorganic nanoparticles [mostly lithium fluoride (LiF) and a little amount of lithium carbonate (Li 2 CO 3 ) and lithium oxide (Li 2 O)], requiring a conformal protective coating to minimize the access of free water molecules . Surface coatings on anode particles with carbon layers, highly fluorinated ether, or aluminum oxide (Al 2 O 3 ) were reported to be effective in improving the cycle life of WIS-based LIBs by suppressing HER. , Here, we report the enhanced performance of WIS-based LIBs by forming carbonaceous layers on TiO 2 (here, we call this as m-TiO 2 ) using biomaterials for the first time in the field. Direct interactions between TiO 2 nanoparticles and microbes have been investigated to determine the photocatalytic antimicrobial/antiviral activities of TiO 2 , , but the application of this composite in aqueous LIBs has not been explored in the field to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…It could be further increased by the reduction of open porosity and by the use of articial SEIs or solvent-free electrolytes. 49,50 In the context of this and many other studies, it must be stressed out that the irreversible processes occurring during SEI formation are likely to have a signicant impact on the pore structure and chemical properties of the electrode materials. It is therefore more reasonable to conclude directly on the structure-property relationships of a material for SEI formation in the rst cycle rather than on the electrochemical signature in the subsequent cycles.…”
Section: Resultsmentioning
confidence: 89%
“…This disadvantage could possibly be minimized by the use of artificial SEIs or solvent-free electrolytes. [40,41] Galvanostatic charge-discharge profiles between 0.0 and 3.0 V (vs Li/Li þ ) of a half cell test at a current density of 0.1 A g À1 are shown in Figure 3c. All curves represent a rather capacitor-like behavior shape dominated by sloping capacity without clear plateaus due to the absence of complete and specific electron-transfer processes between electrode and lithium ions.…”
Section: Resultsmentioning
confidence: 99%